2007
DOI: 10.1016/j.jnt.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

A note on the maximal coefficients of squares of Newman polynomials

Abstract: In a recent paper [G. Yu, An upper bound for B 2 [g] sets, J. Number Theory 122 (1) (2007) 211-220] Gang Yu stated the following conjecture: Let {p i } ∞ i=1 be an arbitrary sequence of polynomials with increasing degrees and all coefficients in {0, 1}. If we denote by (#p i ) the number of non-zero coefficients of p i , and let M(p 2 i ) be the maximal coefficient of p 2 i , then Q := lim inf i→∞ deg(p i )M(p 2 i ) (#p i ) 2 1, ( * ) as long as (#p i ) = o(deg p i ), as i → ∞. We give an explicit example that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Then deg(P ) = N (P ) = 3, H(P 2 ) = H(1+2x+x 2 +2x 3 +2x 4 +x 6 ) = 2, giving Q 2 (P ) = 8/9. Combined with Theorem 1 this implies the main result of [2]. Note that the polynomial 1 + x 2 + x 3 (which is reciprocal to 1 + x + x 3 ) already features as extremal in the following well-known problem: find f (n) = sup N (P )=n, P Newman inf |z|=1 |P (z)|.…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…Then deg(P ) = N (P ) = 3, H(P 2 ) = H(1+2x+x 2 +2x 3 +2x 4 +x 6 ) = 2, giving Q 2 (P ) = 8/9. Combined with Theorem 1 this implies the main result of [2]. Note that the polynomial 1 + x 2 + x 3 (which is reciprocal to 1 + x + x 3 ) already features as extremal in the following well-known problem: find f (n) = sup N (P )=n, P Newman inf |z|=1 |P (z)|.…”
mentioning
confidence: 57%
“…(See Section 4 for some definitions and a discussion concerning B h [g] sets.) Berenhaut and Saidak [2] proved that the condition lim k→∞ N (P k )/deg(P k ) = 0 is indeed necessary in this conjecture. More precisely, they showed that there is a sequence of Newman polynomials for which the above limit is 8/9.…”
mentioning
confidence: 87%
See 3 more Smart Citations